Optimizing Microlearning in English Language Learning: The Role of Learning Involvement and Independence on Vocational School Student Satisfaction - Fera Anita Yuana; Ali Mustofa; Pratiwi Retnaningdyah; Ahmad Munir (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
This study presents the optimization of microlearning in English learning for vocational high school students by emphasizing the role of learning engagement and independence on satisfaction and language skills. The background of the study stems from the low achievement of vocational high school students' English skills and the need for learning strategies that are more adaptive to the characteristics of the digital generation. The purpose of this study is to analyze the influence of microlearning content, learning engagement, and learning independence on English skills and student learning satisfaction, both directly and in complex structural relationships. The method used is a quantitative approach with an explanatory research design through Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis of 300 grade X students of a state vocational high school in Mojokerto. Data were collected through a Likert scale questionnaire and an English proficiency test, then analyzed to test validity, reliability, and the relationship between variables in the structural model. The results showed that learning engagement was the most dominant factor that significantly influenced English skills and learning satisfaction. Microlearning content did not significantly influence English skills, but made a positive contribution to learning satisfaction. Learning independence significantly influenced learning satisfaction, but did not show consistent support for English skills. These findings confirm that successful language learning is determined more by the quality of student interaction and active participation than simply the presentation of digital content. The study's conclusions suggest that microlearning needs to be integrated with interactive learning strategies to achieve optimal results. This research provides important implications for the development of technology-based learning models in vocational education and recommends further research incorporating mediating variables such as motivation and social interaction.